Musculoskeletal Symptoms Associated with Muscular Work in Peach Cultivation Tasks in Norte De Santander - Baldovino, Jorge Iván Anaya; Rangel, Claudia Milena Barrera; Pabón, Blanca Judith Cristancho (Journal of Ecohumanism, 2024)
Introduction: Agriculture is crucial in production throughout the world and a key factor of human activity for the demand for food, which is growing every day. Peach crop workers are susceptible to musculoskeletal symptoms due to strained postures, held postures, antigravitational postures, repetitive movements, heavy lifting. This group of working conditions, added to a number of tasks that can generate difficulties in the health and productivity of the farmer. Objective: To determine the association between musculoskeletal symptoms and muscular work of peach growers in Pamplona, ​​Norte de Santander. Materials and method: Cross-sectional and analytical study. Convenience sampling in which 220 peach growers (Pamplona, ​​Pamplonita, Chitagá, Cacota) participated with the Standardized Nordic Questionnaire for identification of musculoskeletal symptoms, of these, 6 were applied the direct observation method OWAS (Ovako Working Posture Analyzing System), taking routine tasks as a reference. Results: it was identified that the muscular work of the peach cultivation tasks in Norte de Santander are associated with the musculoskeletal symptoms, showing that the task with the highest risk is the collection of pugs and the most affected area of ​​the body in the cultivation tasks. peach is the back. Conclusion: musculoskeletal symptoms are associated with muscular work on tasks in peach cultivation, 13 of which are routine tasks performed for peach cultivation, the highest risk areas for these tasks are the back and legs.